Nanocrystal Aerogels with Coupled or Decoupled Building Blocks - Rusch, Pascal (J Phys Chem Lett, 2019)
[Image: see text] The influence of interparticle contact in nanoparticle-based aerogel network structures is investigated by selectively connecting or isolating the building blocks inside of the network, thereby coupling and decoupling them in regards to their optical and electronic properties. This is achieved by tuning the synthesis sequence and exchanging the point of shell growth and the point of particle assembly, leading to two distinctly different structures as examined by electron microscopy. By thorough examination of the resulting optical properties of the generated structures, the clear correlation between nanoscopic/microscopic structure and macroscopic optical properties is demonstrated. Temperature-dependent measurements and effective mass approximation calculations support our findings.